1999
DOI: 10.1111/1468-5884.00108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angularity of the figures with sharp and round corners on visual evoked potentials

Abstract: Following a study in which equilateral triangles elicited larger visual evoked potentials (VEPs) than either squares or circles, we examined the effect of single-line angular figures with a sharp or a round corner at angles of 45°, 90°, 135°or 180°. VEPs were recorded monopolarly at four locations on the midline of scalp for 10 subjects, while the figure was tachiscopically presented to the lower visual field. Subtracted waves were obtained between figure and control (blank) conditions. N1 (peak latency 135-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…However, the P2 component was consistently driven when the square figures were presented at the outer eccentricity, i.e., 12°. Ito and Sugata (1995), Ito et al (1997Ito et al ( , 1998Ito et al ( , 1999 reported that the amplitude of the component around 100 ms increased according to the sharpness of angularity, but did not offer an explanation about that of the later component above 200 ms. Studying contour perception, Brandeis and Lehmann (1989) reported that the perception of a subjective contour figure induced topographic changes in the anterior-posterior direction and an increase of field strength at latencies of 168-376 ms, even in passive looking.…”
Section: Pattern Recognition In Peripheral Vision Evaluated By Erp Tomentioning
confidence: 94%
See 2 more Smart Citations
“…However, the P2 component was consistently driven when the square figures were presented at the outer eccentricity, i.e., 12°. Ito and Sugata (1995), Ito et al (1997Ito et al ( , 1998Ito et al ( , 1999 reported that the amplitude of the component around 100 ms increased according to the sharpness of angularity, but did not offer an explanation about that of the later component above 200 ms. Studying contour perception, Brandeis and Lehmann (1989) reported that the perception of a subjective contour figure induced topographic changes in the anterior-posterior direction and an increase of field strength at latencies of 168-376 ms, even in passive looking.…”
Section: Pattern Recognition In Peripheral Vision Evaluated By Erp Tomentioning
confidence: 94%
“…The brain activity evoked by geometric figures has been examined in previous VEP studies (Ito and Sugata, 1995;Ito et al, 1997Ito et al, , 1998Ito et al, , 1999. These studies made clear that the sharpness of angularity is related to the amplitude of the early evoked potential.…”
Section: Pattern Recognition In Peripheral Vision Evaluated By Erp Tomentioning
confidence: 99%
See 1 more Smart Citation
“…A triangular pattern had an even higher response than a circle and a square [13]. Sharp corners in patterns had a quicker response than rounded corners [14,15]. Sharpness of patterns were also important; sharp patterns produce quicker visual 2 of 18 response than blurred ones [12].…”
Section: Introductionmentioning
confidence: 95%
“…A similar effect was shown on a positive (P2) wave (averaged peak latency: 240ms), although it was not as distinctive as in the N1 wave. Ito, Sugata, Kuwabara, Wu, and Kojima (1999) adopted the analytical approach and examined the effect of single-lined angular figures with sharp and round corners on transient VEPs. They found that the N1 amplitude tended to decrease as a function of angularity.…”
mentioning
confidence: 99%